Usability evaluation of an academic library website: Experience with the Central Science Library, University of Delhi. Issue 5 (5th October 2015) - Pant, Ankur
Abstract : Purpose: – The paper aims to evaluate the usability of the website of Central Science Library (CSL), University of Delhi. Multi-method approach of evaluation is used with the use of standard checklist and questionnaire survey of representative users. Besides, the information architecture of the website under study is analysed in this paper. Design/methodology/approach: – Based on the literature review and the author's experience, a usability assessment tool for library websites was developed by Pant (2013). It comprises standard checklist and questionnaire for users' survey. In the present study, this framework was used to assess the usability of CSL website. The questionnaire survey of 35 representative users was conducted through random sampling. The results of both methods (standard checklist and questionnaire survey) were analysed for evaluating the website usability. Findings: – Need for improvement of the website was realised in terms of efficiency, effectiveness and learnability for better usability. Notice board, site search facility, list of services, FAQs and user guides were the most sought after features among others as per the analysis of the questionnaire survey. Besides, the need to enhance the visual appeal of the website was felt. However, information resources provided through the CSL website were found useful for users. Originality/value: – The paper presents an innovative multi-method approach of website usability assessment while considering six usability attributes: Usefulness, Efficiency, Effectiveness, Learnability, Satisfaction and Accessibility. The approach adopted in this paper is cost effective in comparison to formal usability tests and heuristic evaluation. Therefore, this framework is suitable for libraries having limited budget to ensure the user-centred library website with maximum usability. This paper encourages other libraries to conduct similar website usability evaluation to identify the usability problem areas and users' perception for their respective website.